Trial by Motive - David Field (Bond Law Review)
This article examines the implications of the High Court ruling in The Queen v Baden-Clay(‘Baden-Clay’)1 for future murder accused with strong motives for killing their spouses who deny all knowledge of their deaths. The article argues that apart from underlining the risk run by any criminal accused who opts to remain silent at their trial, the reasoning of the Court has left open the possibility that a conviction of murder could become a ‘default’ verdict under Queensland law in the absence of clear evidence of manslaughter, once the act of homicide has been proved. It has also provided a ‘pro-Crown’ precedent for future cases in which a conviction may be obtained by means of items of purely circumstantial evidence, not all of which are established beyond reasonable doubt.